How Failure Severity Shapes Consumer Evaluation in the F&B Industry: The Roles of Perceived Responsibility, Consumer Forgiveness, and Repurchase Intention - Kirana Arista Salsabila; Masmira Kurniawati (Advances in Business & Industrial Marketing Research, 2026)
Purpose: This study aims to examine the effect of failure severity on consumer evaluation in the food and beverage industry by analyzing the roles of perceived responsibility, consumer forgiveness, and repurchase intention. Research Method: This study employed a quantitative experimental design with scenario-based stimuli representing high and low failure severity. Data were collected through a survey of university students in Indonesia using non-probability purposive sampling. The study examined the relationships among failure severity, perceived responsibility, consumer forgiveness, and repurchase intention. Data were analyzed using Multivariate Analysis of Variance (MANOVA) and Partial Least Squares Structural Equation Modeling (SEM-PLS). Results and Discussion: The findings indicate that failure severity significantly influences consumer responses across cognitive, affective, and behavioral dimensions. Higher failure severity increases perceived responsibility, decreases consumer forgiveness, and reduces repurchase intention. Perceived responsibility has a positive and significant effect on consumer forgiveness, suggesting that responsibility acknowledgment may signal accountability. Consumer forgiveness also positively affects repurchase intention, indicating that emotional recovery is important in restoring future purchasing behavior. Implications: Firms should manage severe service failures through timely, transparent, and accountable recovery strategies to rebuild trust and encourage repurchase intention. Originality: This study contributes to attribution theory by integrating perceived responsibility, consumer forgiveness, and repurchase intention into the evaluation of service failure.